ҚАРАҚАЛПАҚ ТИЛИНДЕГИ ПАРОНИМЛЕР - Шынназарова, С.Ж.; Оразымбетов, А.; Исмаилова, Д.У. (SCIENCE and SOCIETY, 2017)
The article deals with the study of paronyms in the Karakalpak language. There have been investigated the sound, syllabic, morphological and lexical types of paronyms. The author also studies the difference of paronyms from homophones and distinguishes the variants of literary and dialectic paronyms. On the basis of examples there have been analyzed the peculiarities of paronyms in the Karakalpak language.
Keywords: paronym; homonym; homophon; homophorme; synonym; lexical-semantic; morpheme; dictionary; lexicology; semasiology; pun; linguistics